Interpretasi dan Kebutuhan Pendidik PAUD dalam Intervensi Perilaku Agresif Anak Usia Dini: Studi Deskriptif Kuantitatif - Firqotul Arifah; Muthmainah (Aulad: Journal on Early Childhood, 2025)
This study was motivated because aggressive behavior often occurs in early childhood and is a concern for educators in schools. Aggressive behavior that is left unchecked can disrupt the learning process and interactions with peers in the classroom. This study aims to describe how early childhood educators interpret children's aggressive behavior, the frequency of aggressive incidents, and to determine the needs of educators for a guidebook for interventions for aggressive behavior in children. This research method is quantitative descriptive with a survey. Data collection using a questionnaire via google form with 83 educators as respondents. Data analysis using descriptive statistical analysis including percentage, mean, median, mode, and standard deviation (SD). The results showed that the frequency of educators encountering physically aggressive behavior was quite high, namely 47% almost every day, while verbal and rational aggression was reported rarely. Most educators are aware that untreated aggression can continue into adulthood and believe that good language and positive parenting can reduce aggression.